Studies on the genetic diversity detected by RAPD in the offspring of the nutritional crossbreed between Apis cerana cerana and Apis mellifera ligustica - XIE Xian-bing; SU Song-kun; YAN Wei-yu; GUO Dong-sheng; ZENG Zhi-jiang (浙江大学学报. 农业与生命科学版)
The experiments were conducted with Apis cerana cerana and Apis mellifera ligustica. In this study, nutritional hybridizations were carried out between Apis cerana cerana and Apis mellifera ligustica. Random amplified polymorphic DNA (RAPD) analysis was used to detect genetic diversity of the workers, which were the offspring of parent colonies and hybridization colonies. The results showed that the genetic similarity coefficient between the parent and the nutritional crossbreeding offspring tended to diminish. And some special bands were transferred mutually between Apis cerana cerana and Apis mellifera ligustica. All of these indicate the occurrence of probable gene transfer in honeybees after nutritional hybridization.